(untitled) (International Current Pharmaceutical Journal, 2012)
Paracetamol is a widely used non-prescription analgesic and antipyretic medicine. The study was conducted to assess the comparative in-vitro quality control parameters through the evaluation of weight variation, hardness, friability, disintegration time and dissolution profile between the commercially available tablet brands of paraceta-mol and paracetamol/caffeine combination in Bangladesh. Tablets of five top level manufacturers those have both of the formulations were evaluated in two groups. Both similarities and dissimilarities were found between the groups. All tablets either paracetamol (1.07 to 2.14%) or paracetamol/caffeine (0.98 to 2.09%) showed acceptable weight variation and friability (below 1%). Formulations were somewhat different in their hardness, disintegration time and dissolution profile. All tablets of paracetamol/caffeine were found harder than paracetamol tablets of the same manufacturer. 1 out of 5 for paracetamol and 3 out of 5 for paracetamol/caffeine tablets exceeded the limit of tablet hardness or crushing strength. The disintegration time in 0.1N HCl of paracetamol tablet brands (24 seconds to 4 minutes 52 seconds) were less than the paracetamol/caffeine (6 minutes 33 seconds to 17 minutes 43 seconds) brands. On the other hand in phosphate buffer, pH 7.4, paracetamol/caffeine tablets dissolved quickly and showed better release profile than tablets containing only paracetamol. It can be concluded that standard quality control parameters always should be maintained not only for paracetamol or its combination but also for all kinds of medicine for getting better drug products. DOI: http://dx.doi.org/10.3329/icpj.v1i5.10282 International Current Pharmaceutical Journal 2012, 1(5): 103-109